Sosialisasi Akad Produk-Produk pada Bank Syariah Bersama Masyarakat di Desa Padang Cermin Kabupaten Langkat - Budi Abdullah (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2021)
This article aims to discuss the socialization of products in Islamic banks to the community in Padang Cermin village, Langkat. The methods in this research are counseling, discussion, consultation, and program evaluation. The results of this study indicate that many people already know about Islamic banking products and sharia contracts, but do not know them in depth. The existence of Islamic banking socialization has actually helped the community in Padang Cermin village, Langkat Regency, to get to know more and more details of Islamic banking products. The socialization of sharia banking products also provided an increase in knowledge, skills and understanding of the community in Padang Cermin village, Langkat